Przedwieczni z gwiezdnego płomienia. "Prawda" Stanisława Lema jako horror kosmiczny - Kukulak, Szymon Piotr (Zagadnienia Rodzajów Literackich, 2025)
The paper explores a case study of Stanisław Lem’s short story The Truth, initially published in 1964 (and not translated into English until 2021), which is among his lesser-known works and represents a notable gap in present day literary analyses focusing on Lem’s associations with horror. The paper argues that the short story in question (as probably the only one in the author’s oeuvre) could be identified as an instance of cosmic horror — akin in style to H.P. Lovecraft’s writings — despite the presence of conflicting tropes, which otherwise suggest a more traditional “invention story” framework. Utilizing Lem’s own theoretical framework for differentiating horror from science fiction or fantasy — rooted in the nature of principles governing fictional worlds, as drawn from Roger Caillois’s earlier model — the paper examines those conflicting tropes at both a literary level and, more importantly, at a world-building level. In the latter case, the article points out multiple instances of intentional realism violations, which sharply contrast with Lem’s typical ‘hard science fiction’ formula of the day; violations that could be found in such distant domains as microbiology, astrophysics, or theory of evolution. In the latter case, the paper introduces the concept of “pyroevolution”, akin to “necroevolution” found The Invicible, as a potential explanation for the story’s logic of events. Finally, the paper analyses the references to real-life plasma physics and thermonuclear fusion experiments, from which Lem borrows a majority of technical staffage of the story. The findings suggest that The Truth exemplifies a sophisticated literary game between the author and the reader, wherein real-life scientific elements are subtly distorted to better serve the needs of the horror genre — a very distinctive approach in Lem’s prose, also present in his far better known works, such as Solaris or His Master’s Voice.